The internet as a source of knowledge about soil cover of Poland - Świtoniak, Marcin; Augustyniak, Dawid; Charzyński, Przemysław (Bulletin of Geography. Physical Geography Series, 2018)
The aim of this paper is to assess the quality and correctness of information on Polish soils available on selected websites. Particular attention was paid to educational portals, which became the subject of evaluation of the information its contains in terms of the correctness, up-to-dateness and reliability. Twenty-five websites representing educational portals and blogs were selected for analysis in terms of their contents (type of subject matter) correctness (substantial value), curentness (presence of up-to-date information) and completeness. Most of the information on the evaluated educational portals is targeted at high school students. These websites present only basic content. The most frequent issues on the analyzed portals were: soil types and soil systematics, distribution of soils in Poland, definition of soil and also soil valuation classes. Websites addressed to university students constitute a decided minority, could be said, that even an exception. One of those is article on Wikipedia, which has the highest educational value among all analysed websites.